Feresa attenuata Gray 1874 - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
27. Pygmy Killer Whale Feresa attenuata French: Orque pygmée / German: Zwergschwertwal / Spanish: Orca pigmea Other common names: Slender Blackfish, Slender Pilot Whale Taxonomy. [leresa attenuata Gray, 1874, “South Seas.” This species is monotypic. Distribution. Cosmopolitan tropical and subtropical distribution between ¢.40° N and ¢.35° S, including the Gulfof Mexico and Arabian Sea. Descriptive notes. Total length 210- 260 cm; weight up to 225 kg. Neonates are ¢.80 cm long and weigh 15-20 kg. Male Pygmy Killer Whales may be slightly larger than females. The Pygmy Killer Whale has moderately robust body that tapers posteriorly into shallow tailstock. Head is bulbous and rounded, with no visible beak, and flippers are slender and slightly curved, with rounded tips. Dorsalfin, positioned about halfway along body, is tall and falcate. The Pygmy Killer Whale has dark-gray to black skin, with dark, narrow dorsal cape that dips below dorsal fin, contrasting with slightly paler gray flanks. Lips may be pale gray to white, and a narrow white patch runs ventrally along body, widening at urogenital area. Older adult Pygmy Killer Whales usually have scars over back and flanks from cookie-cutter sharks (Zsistius spp.). There are 11-13 pairs of large, pointed teeth in upperjaw and 8-11 pairs in lower jaw. Habitat. Offshore, deep water, associated with warm currents of tropical origin. The Pygmy Killer Whale is widely distributed, but it does not appear particularly abundant in any region. It is relatively boat-shy, so lack of data could simply be due to limited observation opportunities. The Pygmy Killer Whale does seem to prefer tropical climates, and most observations in higher latitudes have been associated with warm water currents. Itis primarily found in offshore, deeper waters and most frequently observed in the eastern Pacific Ocean, offJapan, and off Hawaii. Food and Feeding. The Pygmy Killer Whale is thought to forage mostly on cephalopods and fish. Commonly documented prey in carcasses from strandings and ...